(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This project is a smoke detector using Arduino for barangay hall of nag-kaisang nayon. This project is one of the safe technologies; the researchers chose this project to give extra protection or safety to every person in the establishment or on one property. A smoke detector is a device that senses smoke, typically as an indicator of fire; it is usually housed in a plastic enclosure device that is used to alarm occupants in a building, detecting a fire before it reaches a spreading stage or attempts to extinguish it. On sensing smoke, the detectors emit a loud sound, a high-pitched alarm tone. The proponents created a smoke detector that can help resolve the client’s issues by managing risk and notifying the safety and security department that there is a fire, smoke, or chemical leak in the facility or establishment. The Smoke Detector is qualified to do its simple task and has features that can protect and give safety precautions to the client. It is very convenient to use because the client only has to put this device in place, and that is prone to fire exposure.